1584. CARISEL A Hybrid III Implementation Effectiveness Study of implementation of Cabotegravir plus Rilpivirine Long Acting (CAB+RPV LA) in EU Health Care Settings Key Clinical and Implementation Outcomes by Implementation Arm. (15th December 2022) - De Wit, Stephane; Rami, Agathe; Bonnet, Fabrice; DeMoor, Rebecca; Bontempo, Gilda; Latham, Christine; Gill, Martin; Hadi, Monica; Cooper, Owen; Anand, Savita Bakhshi; Gutner, Cassidy; Ait-Khaled, Mounir; et al.
Abstract: Background: Cabotegravir + Rilpivirine Long Acting (CAB+RPV LA) every 2 months is a recommended regimen in European and US treatment guidelines for PLWH with virological suppression and no known resistance to CAB or RPV. CARISEL, an implementation study, is the first study where all participants switched from standard oral therapy to 2 monthly CAB+RPV. Key clinical and implementation secondary endpoints are reported. Methods: This single arm study enrolled virologically-suppressed PLWH to receive CAB+RPV LA 2-monthly at 18 clinics in 5 EU countries, conducted from Sept 2020-Feb 2022. Clinics with no prior experience with CAB+RPV LA were preferentially selected. Sites were randomized to standard implementation (Arm-S) or enhanced implementation (Arm-E) which included additional implementation strategies. Proportion of participants with plasma HIV-1 RNA ≥50c/mL and < 50c/mL at Month 12 (FDA Snapshot algorithm, ITT-E) were reported. Adverse events, COVID-related events, clinic visit length, and safety were analyzed by implementation arm. Results: 72% of clinics (13/18) had no experience with CAB+RPV LA at study start. 430 enrolled and treated participants were included with 25% female, 18% black, and a mean baseline age of 44 yrs (30% > 50 years). At Month 12, 87% of participants maintained virologic suppression in each implementation arm (Table 1) and 1 participant (1/430; 0.23%) in Arm-E experienced confirmed virologic failure. Grade 1–2 AEs were reported in Arm-E:99% vs Arm-S: 97%; Grade 3–4 drug-related AEs reported in Arm-E: 4%, Arm-S: 8%. ISRs were reported in 86% of participants; 98% were mild or moderate, median duration of 3 days and a low proportion of participants discontinued treatment due to ISR (6%). Total time in clinic decreased more in Arm-E than Arm-S; visit length varied by country (Table 2). COVID was diagnosed in 16% of participants. COVID-19 related protocol deviations reported in 3% of participants. There were no discontinuations and no snapshot failures due to COVID-19. Conclusion: Regardless of implementation arm, CAB+RPV LA was a highly effective and well tolerated, consistent with clinical outcomes in the Phase 3 clinical program. Clinic visit lengths varied by country and decreased over time. COVID-19 did not lead to treatment disruption or study discontinuation. Disclosures: Stephane De Wit, PhD, AstraZeneca: Grant/Research Support Fabrice Bonnet, PhD, Gilead: Grant/Research Support|Gilead: Honoraria|MSD: Grant/Research Support|MSD: Honoraria|ViiV Healthcare: Grant/Research Support|ViiV Healthcare: Honoraria Rebecca DeMoor, M.S., GlaxoSmithKline: Employee Gilda Bontempo, MD, ViiV Healthcare: Employee|ViiV Healthcare: Stocks/Bonds Christine Latham, MS, ViiV Healthcare: Employee|ViiV Healthcare: Stocks/Bonds Martin Gill, BSc, GlaxoSmithKline: Employee Monica Hadi, PhD, Evidera: Employee Savita Bakhshi Anand, PhD, Evidera: Employee Cassidy Gutner, PhD, ViiV Healthcare: Employee Mounir Ait-Khaled, PhD, GlaxoSmithKline: Stocks/Bonds|ViiV Healthcare: Employee Jean A. van Wyk, MB, ChB; MFPM, ViiV Healthcare Limited: I am an employee of ViiV Healthcare|ViiV Healthcare Limited: Stocks/Bonds Maggie Czarnogorski, MD MPH, ViiV Healthcare: Employee|ViiV Healthcare: Stocks/Bonds.